Understanding and preventing sexual and gender-based violence among South African youth during public health crises - Miriam Hartmann (2025)
The COVID-19 pandemic has had far-reaching consequences beyond the immediate threat of infection, exacerbating existing social inequalities and vulnerabilities, particularly in low- and middle-income countries. Among these, the risk of sexual and gender-based violence (SGBV) among young people emerged as a critical public health concern. This doctoral thesis investigates the impact of the COVID-19 crisis on SGBV exposure among adolescents and young adults aged 10-24 in South Africa-a country with high baseline rates of SGBV and stringent lockdown policies during the pandemic.The thesis is structured around four sub-studies embedded within two overarching studies: a longitudinal mixed-methods cohort of young people with and without HIV (the BUDDY study (Sub-studies l-II)) and a cluster randomized controlled trial assessing the impact of an empowerment-based self-defense intervention for girls (the No Means No (NMN) evaluation (Sub-studies III-IV)). Using a combination of quantitative and qualitative methods, the research explores the trajectories of SGBV during and after lockdowns, the psychosocial and structural drivers of violence, and the potential of targeted interventions to mitigate violence in public health crisis contexts.Findings from Sub-study I highlights a complex pattern of violence exposure, with notable perceived increases in community and household violence during the initial lockdown period. Risk factors such as common mental disorder symptomology, unemployment/being out of school, and food insecurity were associated with higher exposure to SGBV among youth. Trajectory modeling revealed distinct subgroups of youth experiencing persistent or fluctuating patterns of violence, influenced by mental health, and socioeconomic factors (Sub-study II).The NMN evaluation demonstrated that an 8-hour, COVID-adapted Empowerment Self-Defense curriculum had a positive impact on self-defense knowledge, and perceived feelings of confidence and sources of support among adolescent girls. However, the trial did not find statistically significant differences in sexual violence exposure across arms at 12-month follow-up (Sub-study III). Qualitative findings suggest that contextual and implementation barriers-such as school disruptions and limited time for skill reinforcement-may have influenced outcomes (Sub-study IV).This research contributes new longitudinal and intervention-based evidence on youth SGBV during a global public health crisis. It underscores the importance of addressing mental health, and socioeconomic drivers of SGBV as part of prevention strategies. It also calls for trauma-informed, contextually grounded interventions that are responsive to specific risk factors exacerbated in times of widespread social instability. The findings hold important implications for public health policy, education systems, and SGBV prevention programming in South Africa and similar settings.List of scientific papersI. Hartmann, M., Giovenco, D., Zeebari, Z., Itzikowitz, G., Ekström, A.M., Nielsen, A., Pettifor, A., Bekker, L.G. and Kågesten, A.E., 2023. Associations between psychosocial wellbeing and experience of gender-based violence at community, household, and intimate- partner levels among a cross-sectional cohort of young people living with and without HIV during COVID-19 in Cape Town, South Africa. BMC public health, 23(1), p.2115. https://doi.org/10.1186/s12889-023-16945-5II. Hartmann, M., Stoner, M.C., Storey, S., Giovenco, D., Zondi, Y.Z., Qwabe, N., Ekström, A.M., Pettifor, A.E., Bekker, L.G. and Kågesten, A., 2025. Mixed-method longitudinal investigation of sexual and gender-based violence following COVID-19 in South Africa. BMJ public health, 3(1).https://doi.org/10.1136/bmjph-2024-001697III. Hartmann, M., Mutangabende, S., Nash, S., Browne, E.N., Hatcher, A., Kågesten, A.E. and Roberts, S.T., 2025. Effectiveness of an empowerment-based self-defense program among South African girls: results from a cluster-randomized control trial in schools. BMC Women's Health, 25(1), p.119. https://doi.org/10.1186/s12905-025-03647-wIV. Hartmann, M. Wallengren, E., Mutangabende, S., Goba, M., Hatcher, A., Roberts, S.T., and Kågesten, A. Adolescent girls' embodied experiences with an empowerment-based self-defense intervention for sexual violence prevention: a qualitative study in Gqeberha, South Africa. [Submitted]